Du, som går ud fra den levende Gud - Balslev-Clausen, Peter (Grundtvig-Studier, 1983)
O Thou that dost Flow from the One Living God... By Peter Balslev-Clausen When Grundtvig produced his Song-Work for the Danish Church (1836-37), he based his choice of hymns for translation on the theory of the Seven Churches of Christendom, which he supported from the letters to the Churches in Revelation 2-3. Grundtvig identified the fourth Church in Thyatira with the Anglo- Saxon/English Church and altogether included 40 translations from Anglo-Saxon and English. Most of the English hymns that Grundtvig translated for inclusion were from his own time, including James Montgomery’s evangelical hymn ‘O Spirit of the Living God’ from 1823. Grundtvig translated this hymn as Du, som gaaer ud fra den levende Gud (O Thou that dost Flow from the One Living God), and placed it as number 360 in the section on Whitsun hymns. A comparison between Montgomery’s hymn and Grundtvig’s translation shows that Grundtvig has been both loyal to and free with his adaptation. He changes both the metre and the structure of the hymn: the metre is now dactyls for iambics, and the structure is altered from parallels in which the halves complement one another to a V-structure. These changes make the hymn more living and more dynamic. As regards language and content Grundtvig’s translation accords on a number of points with the translations placed immediately before this hymn, not least in the thematic distinctions between light and dark, life and death, God and the Devil. Montgomery’s hymn takes the form of a prayer and is kept in the imperative, whereas Grundtvig’s translation offers a number of interpolations in the indicative to delineate the divine and the human background for the prayer. An analysis of Grundtvig’s translation reveals that is interwoven to a much greater degree than Montgomery’s original with biblical references, partly general, partly taken from Easter and Whitsun sermon texts. There are a number of similarities between Grundtvig’s translations and his sermons, especially from Ascension Day to the First Sunday after Trinity, and in particular with regard to his thoughts on the Holy Spirit and rebirth. Finally on the basis of Grundtvig’s remarks to Nugent Wade, the English rector of Elsinore at the time, Grundtvig’s final words in verse 6 on ‘the heirs of damnation’, are compared with parallel declarations in the sermon from the early summer of 1837. ‘O Thou that dost Flow from the One Living God’ is a good example of how Grundtvig’s hymns come into being in relation to everything else he is thinking and speaking about while he is writing them. At the same time we see how it is in the hymns, as in the rest of his poetry, that Grundtvig’s ideas and feelings find their clarified form. In the hymns he experienced the dramatic and liturgical unity with God and man and thus with himself, a unity to which his ecclesiastical and theoretical prose and his biblical reading led towards but could not in themselves attain. It is of no consequence in this connection whether the hymn is Grundtvig’s own or, as is the case with ‘O Thou that dost Flow from the One Living God’, an adaptation from a foreign original. Through his reworking of the hymn Grundtvig makes it his own, and a comparison with the original proves only how very independent he was in his hymn writing.